Bioequivalence study of FlunacTM and DiflucanTM in healthy Bangladeshi male volunteers - Sarker, UK; Misbahuddin, M; Hossain, MA (KYAMC Journal, 2013)
A bioequivalence study of a local antifungal drug, fluconazole (FlunacTM), was compared with that of innovator product DiflucanTM. The study was conducted on 15 healthy volunteers and single cross-over dose of 150 mg fluconazole was administered orally. Two milliliter of blood was collected at different time intervals for 96 hours. The drug was extracted by liquid-liquid extraction and estimated by high performance liquid chromatography with diode array detector (260 nm). The chromatographic separation was accomplished using C18 analytical column with a mobile phase consisting of water and acetonitril (80:20, v/v). The Cmax of DiflucanTM and FlunacTM was 2.48 ± 0.29 g/mL and 2.23 ± 0.29 g/mL respectively. The Tmax of DiflucanTM and FlunacTM was 2.18 ± 0.98 hours and 2.56 ± 0.81 hours respectively. The area under the curve (0 to 96 hours) of DiflucanTM and FlunacTM was 73.28 ± 13.80 hours/mL and 74.49 ± 16.03 hours/mL. The half-life of both the drugs was 44.59 ± 13.79 hours for DiflucanTM and 42.73 ± 11.71 hour for FlunacTM. This study shows that FlunacTM is comparable to DiflucanTM in pharmacokinetic aspect. DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13255 KYAMC Journal Vol.2(2) January 2012, 159-163